CARA PENANGGULANGAN MIRAS DIKALANGAN PEMUDA KRISTEN BERDASARKAN YESAYA 5:22-24 - Hermanto, Abang; Hidayati, Ermin (Sekolah Tinggi Teologi Pelita Hati, 2024)
Alcohol abuse among Christian youth is a serious problem that requires appropriate treatment. This article aims to explore ways to overcome this phenomenon, by referring to the Book of Isaiah 5:22-24. The meaning and implications of these verses in the context of overcoming alcohol abuse among Christian youth will be analyzed. Analysis will include an understanding of the punishments mentioned in the text, as well as spiritual and practical strategies that Christian youth can employ to avoid temptation and change harmful behavior. Relevant keywords include alcohol abuse, Christian youth, the Book of Isaiah, coping, spirituality, and behavior change. This research aims to provide meaningful guidance for Christian youth in overcoming the problem of alcohol abuse, as well as to support them in building a healthy lifestyle that is in line with the values of their faith. Thus, overcoming alcoholism among Christian youth is not only an individual responsibility, but is also part of a collective effort to build a better society.